Evaluation of glass formation and critical casting diameter in Al-based metallic glasses. (25th December 2015) - Liao, J.P.; Yang, B.J.; Zhang, Y.; Lu, W.Y.; Gu, X.J.; Wang, J.Q.
Abstract: Critical cooling rate R c for a series of Al-based glass formers, as well as cooling rate T ′ for copper-mold casting Al-based bulk metallic glass (BMG) samples, have been calculated. It is found that the glass forming ability (GFA) is reflected by the change of R c value, and Al86 Ni6 Y4.5 Co2 La1.5 alloy, the best glass former in Al-based systems, holds the lowest R c of about 3.01 × 10 3  K/s. The T ′ for the rod sample is determined by casting diameter D . When synthesizing Al-based BMGs, with the D increases from 1 mm to 3 mm, the value of T ′ decreases from 7.48 × 10 3  K/s to 0.83 × 10 3  K/s. Based on these calculations, the critical casting diameter D c for a certain Al-rich multi-composition could be predicted. Further, for the composition Al86 Ni6 Y4.5 Co2 La1.5, bulk glassy sample with D c up to 1.5 mm has been obtained, confirming the theoretical prediction. Graphical abstract: Highlights: Defining the GFA of Al-based metallic glasses through calculation The cooling process for copper mold casting has been analyzed. The evaluation criterion for casting a certain sized sample has been proposed. Critical casting diameter for Al86 Ni6 Y4.5 Co2 La1.5 is 1.5 mm.